Enabling factors for cooperation in the climate negotiations: a comparative analysis of Copenhagen 2009 and Paris 2015 - Maximilian Högl (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
Interdisciplinary research shows that, in contrast to the assumptions of the “homo oeconomicus” paradigm, human beings frequently cooperate in the face of common-pool resource problems and public-good dilemmas. Seven factors that drive cooperation in these scenarios have been found: trust, communication, reputation, fairness, enforcement, we-identity and reciprocity. However, can these insights be transferred to the discipline of international relations, where not just individuals, but also nation states interact? As climate change constitutes a global-scale, common-pool resource problem, climate negotiations provide a great playing ground to examine the transferability of the theory of enabling factors for cooperation to the level of international relations. This paper undertakes a first attempt at this, comparing two high-level climate summits: COP 15, which took place in Copenhagen in 2009, and COP 21, which was held in Paris in 2015. It is asked whether it is plausible to argue that the failure of COP 15 to produce a generally accepted agreement and the respective success of COP 21 can be explained by a change in the provision of enabling factors for cooperation? A mixed methodological approach is applied: Interviews with official country delegates representing developing and developed countries are conducted as a first step, and the reports of the Earth Negotiations Bulletin (ENB) are analysed as a second step. Although the cooperation patterns and rates of reciprocation can be examined and visualised based on a coding system of the ENB reports, the interviews provide a deeper understanding of the causality behind the observations. The major changes between COP 15 and COP 21 took place in the fields of communication and trust, enforcement and fairness, reputation and reciprocity. The factors communication and trust are strongly affected by the performance of the COP presidency, which has the role of facilitating the process. The negotiations during COP 15 were perceived as being non-transparent and exclusive, which resulted in a lack of trust towards the presidency. Furthermore, a high envisaged level of enforcement in the form of a “global deal” with legally binding emission-reduction obligations resulted in distributional conflicts. A situation of mutual blame-shifting and exclusively negatively reciprocal relations between developed and developing countries ensued. During COP 21, in contrast, the presidency built trust by communicating transparently and cultivating a manner of listening to all parties equally. The envisaged level of enforcement was lowered, and the allowance for self-differentiation based on “nationally determined contributions” sidelined impeding fairness debates. Reputation was used as a negotiation strategy, and several positive reciprocal relations between developed and developing countries emerged, maintaining and deepening cooperation. Even though climate negotiations are shaped by many exogenous factors, it can be argued that an agreement in Paris would not have been possible without these changes in the provision of enabling factors for cooperation. Besides these major findings, this paper provides evidence for the role of informal communication and personal relations at the negotiations. Therefore, it also offers interesting insights into the behind-the-scenes dynamics that are not captured in official reports.
Keywords: 330; Regionale + globale + transnationale Governance; Klimawandel